1980
DOI: 10.1051/rnd:19800618
|View full text |Cite
|
Sign up to set email alerts
|

The control of male fertility by 6-chloro-6-deoxysugars

Abstract: Summary.1. 6-Chloro-6-deoxyglucose (24 mg/kg/day) produces a rapid and reversible antifertility effect in the male rat but high doses (> 200 mg/kg/day) produce spermatocoeles. In the mouse repeated high doses (480 mg/kg/day) cause paralysis of the hind limbs but there is no effect on fertility.2. Spermatozoa from rats treated with 6-chloro-6-deoxyglucose (24 mg/kg/day) are unable to metabolize glucose and rapidly become exhausted when glucose is the only substrate supplied. Glycolysis is inhibited at the glyce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…The emphasis of these investigations was on the site of attack of at-chlorohydrin, especially on the metabolism of sperm [32,33]. To date, the only available data on changes in epididymal proteins caused by (x-chlorohydrin and 6-chloro-6-deoxyglucose, a metabolite also inhibiting the activity of glyceraldehyde 3-phosphate dehydrogenase in rats in a manner similar to achlorohydrin [34,35], are from Tsang et al [36], who investigated the effect on epididymal protein secretion and the acquisition of sperm surface proteins by D gel electrophoresis. They found that protein patterns of cauda epididymidal fluids from treated animals were similar to those from control animals, but there were some quantitative changes concerning iodination of sperm surface proteins.…”
Section: Discussionmentioning
confidence: 98%
“…The emphasis of these investigations was on the site of attack of at-chlorohydrin, especially on the metabolism of sperm [32,33]. To date, the only available data on changes in epididymal proteins caused by (x-chlorohydrin and 6-chloro-6-deoxyglucose, a metabolite also inhibiting the activity of glyceraldehyde 3-phosphate dehydrogenase in rats in a manner similar to achlorohydrin [34,35], are from Tsang et al [36], who investigated the effect on epididymal protein secretion and the acquisition of sperm surface proteins by D gel electrophoresis. They found that protein patterns of cauda epididymidal fluids from treated animals were similar to those from control animals, but there were some quantitative changes concerning iodination of sperm surface proteins.…”
Section: Discussionmentioning
confidence: 98%
“…This is probably because we included 0-1% Triton X-100 in the extraction media but did not include a low speed centrifugation step before assaying the homogenates. The activities given by Brooks (1977) would not be adequate to explain the rate of respiration by rat epididymal spermatozoa in the presence of added substrates (Ford & Waites, 1980). Sodium arsenite was expected to inhibit both pyruvate dehydrogenase (EC 1.2.4.1) and 2-oxoglutarate dehydrogenase (Webb, 1966) and its effect was specific since it did not significantly decrease the production of lactate from glucose or the ability of the spermatozoa to obtain ATP from this process.…”
Section: Discussionmentioning
confidence: 99%
“…However, high doses of -chlorohydrin are required to inhibit the oxidation of acetate, pyruvate or lactate by ram spermatozoa (Brown-Woodman et al, 1978). Moreover, spermatozoa from rats treated with 6-chloro-6-deoxyglucose (24 mg/kg/day), which has an antifertility effect similar to that of -chlorohydrin (Ford & Waites, 1978), can remain motile and retain a high energy charge when supplied with 2 mM-pyruvate plus 4 mM-DL-lactate as substrates although these parameters decline rapidly when 2 mM-glucose is the only substrate given (Ford & Waites, 1980). Therefore, unless spermatozoa are compelled to metabolize sugar at some stage, e.g.…”
Section: Discussionmentioning
confidence: 99%